Pineapple leaf fibers and PALF-reinforced polymer composites - Salit, Mohd. Sapuan; Mohamed, Abd. Rahman; Siregar, Januar Parlaungan; Ishak, Mohd. Ridzuan (Springer-Verlag, 2011)
Pineapple leaf fibers (PALF) have long been known as textile materials in many countries. Despite being mechanically excellent and environmentally sound, PALF are the least-studied natural fibers, especially for reinforcing composites. This article presents a survey of research works carried out on PALF and PALF-reinforced composites. It reviews PALF extraction, fiber characterization, and PALF applications, modification of PALF, and manufacture and properties of PALF-reinforced composites. With increasing importance of pineapple and pineapple plantation area, value-added applications of PALF as reinforcing fibers in polymer composites must be developed in order to increase “resource potential” of pineapple and consequently energize the utilization of PALF.